Leaders and outliers in the race of regions - EU Cohesion Policy in Poland in the light of macroeconomic modelling - Zbigniew Mogiła; Janusz Zaleski; Joanna Kudełko (European Regional Science Association (ERSA), 2011)
Since Poland has benefited from cohesion policy since accession to the EU in 2004, and is currently the largest national beneficiary of EU cohesion policy expenditure in the financial perspective 2007-2013, analysis of the impact of the EU funds in this country seems to be an important part of the overall evaluation of this policy. The outcome is especially interesting at the beginning of the debate on the future of EU cohesion policy the results of which will certainly have an effect on the development of many regions in the EU. In our analysis we concentrate on the three Polish NUTS-2 regions: Mazowieckie- capital region with the overwhelming economic supremacy, DolnoÅlÄ…skie- one of the leading Polish regions, ÅšwiÄ™tokrzyskie - representative of the regions lagging behind the Poland's average in terms of socio-economic development. The main aim of this paper is not simply to compare and contrast the impacts of EU cohesion policy on the above mentioned regions, but also to confront them with the theoretical expectations. The analysis is carried out using such macroeconomic indicators as GDP per capita, employment, labour productivity and it focuses on the period 2004-2020 in order to capture both short- and long-term effects of the EU intervention. Our research draws on the regional HERMIN macroeconomic models of Mazowieckie (HPL5MZ), DolnoÅlÄ…skie (HPL5DL) and ÅšwiÄ™tokrzyskie (HPL5SW) which are regionalised versions of the Polish national HERMIN macroeconomic model (HPL5)- part of the Cohesion System of HERMIN Models (CSHM) used by the European Commission. The results of our analysis point to the role of EU cohesion policy in the process of socio-economic convergence both at the national and European level. However, they are presented from a perspective of the three Polish regions characterized by the different levels of socio-economic development in order to show how EU funds affect economic leaders and outliers of the country. On the basis of the conducted analysis several conclusions are drawn with regard to macroeconomic modelling at the regional level which might be used to improve robustness and credibility of the evaluation of EU cohesion policy.
Keywords: 330